Case Study of the Implementation of the Independent Curriculum at SD Negeri 02 Palembang - Yuliana Yuliana; Tri Widayatsih; Mulyadi Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to comprehensively describe how the Independent Curriculum is implemented at SD Negeri 02 Palembang, particularly in the planning, implementation, and evaluation stages of learning. The Independent Curriculum itself is a new policy in Indonesian education that emphasizes student-centered learning, character building, and provides more flexibility for teachers to design learning processes according to the context and needs of students. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, direct field observations, and documentation of learning activities. Key informants consisted of the principal, several teachers, and students from the upper grades. The results showed that the planning of the Independent Curriculum at SD Negeri 02 Palembang was carried out collaboratively, with the development of teaching modules and learning tools tailored to predetermined learning outcomes. In practice, learning takes place in a participatory manner with a variety of approaches, including the use of project-based methods designed to develop the Pancasila Student Profile in students. Learning evaluation is conducted continuously through formative and summative assessments, supported by diagnostic assessments that assist teachers in designing strategies for future learning improvements. Although the implementation of the Independent Curriculum faced several obstacles, such as limited resources and uneven teacher understanding of the new curriculum, the school remains strongly committed to implementing the Independent Curriculum in a phased and sustainable manner.